Lipoprotein (a) as a cause of statin-resistance: how to treat? – Case report - Négrier Lourenço, Carolina (2009)
Lipoprotein (a) (Lp(a)) is considered to be a cardiovascular risk factor, and nicotinic acid is the only available drug that reduces its levels.The authors present the case of a 44-year-old male patient with hypercholesterolemia that responded poorly to statin therapy. After identifying elevated Lp(a) levels combined therapy with nicotinic acid was initiated, resulting in normalization of LDL-cholesterol levels. The authors also make a theoretical review of Lp(a) and nicotinic acid.